2002
DOI: 10.1103/physrevlett.88.147403
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Transitions of the Charge-Induced Reconstruction of Au(110) by Reflectance Anisotropy Spectroscopy

Abstract: Missing-row reconstructions on Au(110) immersed in electrolytes have been studied by in situ reflectance anisotropy spectroscopy. Transitions between the 1 x 3, 1 x 2, and 1 x 1 surface structures were monitored as a function of the applied potential. A kinetic model allowed us to reproduce the data satisfactorily. These results confirm the theoretical predictions showing that the surface charge determines the surface reconstruction. The transition potentials and the activation barriers were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
61
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 25 publications
9
61
2
Order By: Relevance
“…Mazine and Borensztein [53,54] find the intensity of the feature observed at 2.6 eV in the spectrum to increase as the potential is made more positive. In our earlier study we observed the intensity of this feature to be reduced as the potential was made more positive [52].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Mazine and Borensztein [53,54] find the intensity of the feature observed at 2.6 eV in the spectrum to increase as the potential is made more positive. In our earlier study we observed the intensity of this feature to be reduced as the potential was made more positive [52].…”
Section: Discussionmentioning
confidence: 95%
“…This difference in the dependence of the spectra on the value of the applied potential lead the two groups to make an opposite assignment of RA spectral profiles to the Au(110) (1 × 2) and (1 × 1) reconstructions since the voltage dependence of the transition between these reconstructions has been established from STM studies [66]. This issue has been discussed [52][53][54][55] and reviewed recently [47] and it is clear that an unambiguous identification of RA spectra with surface reconstructions at Au(110) electrodes in an electrochemical cell has not yet been established. It is likely that the differences observed in the RA spectra arise from differences in the morphology of the Au(110) surfaces.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Detailed investigations regarding this phenomenon for metal/solution interfaces [2] were performed by employing various ex-situ techniques [3,4] such as low-energy electron diffraction (LEED), reflection high-energy electron diffraction (RHEED), and structure-sensitive techniques such as in-situ scanning tunneling microscopy (STM) [5], in-situ X-ray diffraction (XRD) [6] and reflection anisotropy spectroscopy [7]. While studying reconstructed surfaces in an electrochemical environment, it was found that at electrode potentials positive of the potential of zero charge (E pzc ), the reconstruction is lifted and the surface morphology changes to the bulk-truncated structure [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…The ETF 2e is inaccessible on reducing the engineered protein chemically as observed for a wild-type protein [9]. However, the reduction of ETF to the 2-electron reduced species is achievable by electrochemical methods [19]. Protein (63 μM) was contained in 50 mM potassium phosphate buffer, pH 7.0 at 25 °C and maintained under anaerobic conditions.…”
mentioning
confidence: 99%